RNA polymerase II primes Polycomb‐repressed developmental genes throughout terminal neuronal differentiation. Issue 10 (16th October 2017) - Ferrai, Carmelo; Torlai Triglia, Elena; Risner‐Janiczek, Jessica R; Rito, Tiago; Rackham, Owen JL; de Santiago, Inês; Kukalev, Alexander; Nicodemi, Mario; Akalin, Altuna; Li, Meng; Ungless, Mark A; Pombo, Ana
Abstract: Polycomb repression in mouse embryonic stem cells (ESCs) is tightly associated with promoter co‐occupancy of RNA polymerase II (RNAPII) which is thought to prime genes for activation during early development. However, it is unknown whether RNAPII poising is a general feature of Polycomb repression, or is lost during differentiation. Here, we map the genome‐wide occupancy of RNAPII and Polycomb from pluripotent ESCs to non‐dividing functional dopaminergic neurons. We find that poised RNAPII complexes are ubiquitously present at Polycomb‐repressed genes at all stages of neuronal differentiation. We observe both loss and acquisition of RNAPII and Polycomb at specific groups of genes reflecting their silencing or activation. Strikingly, RNAPII remains poised at transcription factor genes which are silenced in neurons through Polycomb repression, and have major roles in specifying other, non‐neuronal lineages. We conclude that RNAPII poising is intrinsically associated with Polycomb repression throughout differentiation. Our work suggests that the tight interplay between RNAPII poising and Polycomb repression not only instructs promoter state transitions, but also may enable promoter plasticity in differentiated cells. Synopsis: Poised RNAPII‐S5p is present at Polycomb‐repressed genes from embryonic stem cells to terminally differentiated neurons. The tight interplay between RNAPII poising and Polycomb repression enables promoter plasticity in differentiated cells and increased potential for reactivation. Poised RNAPII‐S5p primes Polycomb‐repressed promoters throughout terminal differentiation to functional dopaminergic neurons. Poised RNAPII‐S5p associates with increased potential for reactivation upon loss of Polycomb repression. DNA methylation valleys coincide with broad occupancy of poised RNAPII‐S5p and Polycomb repression. Key non‐neuronal transcription factor genes that co‐associate with Polycomb and RNAPII‐S5p in neurons have potential roles in transdifferentiation. Abstract : Poised RNAPII‐S5p is present at Polycomb‐repressed genes from embryonic stem cells to terminally differentiated neurons. The tight interplay between RNAPII poising and Polycomb repression enables promoter plasticity in differentiated cells and increased potential for reactivation.